2022
DOI: 10.1186/s12864-022-08939-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and population structure of glassy-winged sharpshooters (Homalodisca vitripennis) with varying insecticide resistance in southern California

Abstract: Background Homalodisca vitripennis Germar, the glassy-winged sharpshooter, is an invasive insect in California and a critical threat to agriculture through its transmission of the plant pathogen, Xylella fastidiosa. Quarantine, broad-spectrum insecticides, and biological control have been used for population management of H. vitripennis since its invasion and subsequent proliferation throughout California. Recently wide-spread neonicotinoid resistance has been detected in populations of H. vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 95 publications
0
6
0
Order By: Relevance
“…Other factors might contribute to differences across geographic regions, for example, local environmental conditions (e.g., temperature, humidity, and elevation) or host genetics. Though in GWSS, host genetics may only play a small role as no population structure has been detected in Southern California populations possibly due to their relatively recent introduction ( 33 ). Future studies should incorporate local environmental data, as well as collect possible dietary sources, to help identify the most important factors driving these regional patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors might contribute to differences across geographic regions, for example, local environmental conditions (e.g., temperature, humidity, and elevation) or host genetics. Though in GWSS, host genetics may only play a small role as no population structure has been detected in Southern California populations possibly due to their relatively recent introduction ( 33 ). Future studies should incorporate local environmental data, as well as collect possible dietary sources, to help identify the most important factors driving these regional patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Insecticide resistance usually involves multiple coexisting mechanisms spanning behavioral (e.g., avoidance) and physiological processes (e.g., cuticle modifications and detoxification) ( 23 25 ), and studies have proposed a novel role for symbionts and other associated microbes in detoxification of insecticides for their associated hosts ( 26 31 ). Recent studies on Southern California GWSS populations have identified both trade-offs in host reproductive fitness associated with resistance ( 32 ) as well as host genes that may play a role in conferring resistance ( 33 ). However, the possible role of the microbiome and mycobiome in the resistance of these GWSS populations has yet to be fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…The imidacloprid-resistance status is known for 53 of these GWSS from assays of these individuals themselves or other individuals from the same collection date or captive line. Imidacloprid status assays were performed as described in Ettinger et al [33]. Insects were stored in RNAlater (ThermoFisher Scientific, Waltham, MA, USA) or 200 proof ethanol and kept at -20°C prior to processing.…”
Section: Sample Collectionmentioning
confidence: 99%
“…cuticle modifications, detoxification) [23][24][25], and studies have proposed a novel role for symbionts and other associated microbes in detoxification of insecticides for their associated hosts [26][27][28][29][30][31]. Recent studies on Southern California GWSS populations have identified both trade-offs in host reproductive fitness associated with resistance [32] as well as host genes that may play a role in conferring resistance [33]. However, the possible role of the microbiome and mycobiome in the resistance of these GWSS populations has yet to be fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptome sequencing is a second-generation sequencing platform to obtain almost quickly and comprehensively all transcripts and gene sequences of a specific cell or tissue of a species in a particular state, which can be used to study gene expression, function, structure, alternative splicing, and new transcript prediction. At present, transcriptome sequencing has been widely used in basic research, clinical diagnosis, and drug discovery [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%